Subjectivity, Intersubjectivity and Temporality in Meaning-Making of Sexual Desire - Camincher, Agnès (International Review of Theoretical Psychologies, 2026)
In the history of philosophy and psychology, the relationship between subjectivity and sexual desire has been explored from various perspectives. However, the processes of meaning-making related to sexual desire remain partially unknown, despite being central to contemporary debates. This study aims to provide a detailed and evidence-based discourse on the psychic dimensions of sexual desire. The study begins with a historical and theoretical review of differing perspectives on sexual desire. It then focuses more specifically on the problem of the relationship to the Other in naturalistic conceptions of desire. This discussion is supported by a case study. The case study is part of a broader qualitative research project based on the accounts of sexology patients consulting for issues related to sexual desire. Out of 256 interviews with 25 participants, 105 interviews from 22 participants were selected. Only excerpts concerning the meaning of sexual desire were transcribed and analyzed using a dialogical approach. Results reveal that the construction of the meaning of sexual desire involves temporality, micro-events, and relationships with Others. More specifically, the detailed analysis of the case study highlights the psychological and ethical consequences of naturalistic representations of desire, which frame desire as monological.